Correction: Distance, accessibility and costs. Decision-making during childbirth in rural Sierra Leone: A qualitative study. - Laura Treacy; Håkon A Bolkan; Mette Sagbakken (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0188280.].